Bioactivity of Sengkubak (Pycnarrhena cauliflora Diels.) Leaf Ethanolic Extract as Antioxidant and Antibacterial Streptococcus Sanguinis - Cicilia, Cindy Oktavi; Yudianto, Ahmad; Putri, Rury Eryna (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Pycnarrhena cauliflora Diels. known as Sengkubak, is a natural-based potential antioxidant and antibacterial from the Menispermaceae family. Streptococcus sanguinis is a primary colonizer bacteria that is consistent in biofilm formation. This study attempted to identify S. sanguinis inhibition from antibacterial and antioxidant bioactivity of sengkubak leaf extract. Sengkubak leaves samples were extracted with 70% ethanol through 72 hours (3x24) maceration. Phytochemicals were identified qualitatively and quantitatively through analysis of total quercetin and phenolic content. Antioxidants were tested using the DPPH method. S. sanguinis sensitivity was tested through liquid microdilution method. The extract of sengkubak leaves has a yield of 16.30% (w/w). Qualitative screening showed positive results for flavonoids, phenols, alkaloids, saponins, terpenoids, tannins, and steroids. TFC (quercetin) in extract was 5.22±0.969 QE/g and TPC was 4.08±1.005 mg GAE/g. The IC50 antioxidant value of extract was 40.136 µg/mL. The minimum inhibitory concentration value is shown at 5×10⁴ µg/mL. This research study proves that ethanol extract of sengkubak leaves holds various phytochemical compounds which are likely utilized as potent antioxidants and have inhibitory effect against S.sanguinis.